The influence of environmental factors on clinical pathological changes of patients with immunoglobulin A nephropathy from different areas of China. (15th October 2018) - Fan, Ping; Song, Jianmin; Chen, Qun; Cheng, Xiaohong; Liu, Xusheng; Zou, Chuan; Xie, Bin
Abstract: Objectives: The effects of regional characteristics of IgAN patients in different areas of China were investigated. Methods: Patients who were identified to have primary IgAN by renal biopsy diagnosis were recruited both from Shaanxi province hospital of traditional Chinese medicine and Guangdong province hospital of traditional Chinese medicine. Besides renal histopathology data, a number of clinical and laboratory data were collected. Results: It was shown that the frequency of the patients with no mucosal infection in the urinary tract was higher in the Guangzhou group, while the frequencies of upper respiratory tract and biliary infections were lower when compared with those in the Xi'an group. Serum uric acid, alexin C3, creatinine and serum cholesterol concentrations were increased in the Guangzhou group, while triglyceride, glomerular filtration rate, and urine red blood cell count level decreased. IgA + IgM + C3 and IgA + IgG + IgM + C3 were found in most patients of the Xi'an group, whereas IgA + C3, IgA + IgM + C3 and IgA were more frequent in the Guangzhou group. Conclusion: It was found that differential environment, life habits and patterns in the two investigated areas obviously may influence the variable characteristics of IgAN patients.